KEBIJAKAN EKONOMI UMAR BIN KHATTHAB - Fahlefi, Rizal (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2014)
The leadership of Umar bin Khatthab had showed that the implementation the role (syari’at) of Islam did not stop a nation leader to be creative and innovative to make his country peace and wealth coming true. He had made a farm economy wish and an economy wish in general impartially, tolerantly, and orientally. He developed the priciples of economy in which every one could get his or her right and obligation based on the Koran (Al-Qur’an) and its ordinary. It was done by respecting and helping each other. He also took the advantages of some factors such as production, land, employee, capital, and protecting the individual or group domination.